Pilates for rowers - Shearman, S. (2019)
Rowing is a sport enjoyed by all ages and abilities, from school to club rowing, through to state and national representative, as well as masters and Paralympic categories. It it`s a physically challenging sport, requiring strength, power as well as a high and anaerobic capacities. However, with challenge brings reward and it`s an enjoyable sport be a partof. As with any sport, there is always a risk of injury and it`s important to recognise either what you can do to avoid it or if it`s already occurred; manage and rehabilitate it. Evidence shows us that if you completely remove an injured athlete from training, this is predictive of injury recurrence. Therefore, it is importantto keep up with normal training loads whilst avoiding aggravating positions and prolonged rest. The article presents common Injuries we see with rowers and how Pilates can help.